Tony Conrad. Video - und darüber hinaus - Lurk, Tabea (Peter Lang International Academic Publishing Group, 2015)
Tony Conrad (b. 1940) has been a well-known American artist for more than 50 years. Celebrated as a musician, filmmaker, video and performance artist, he achieved his breakthrough in 1966 with the experimental film The Flicker. In addition to his film work (including the so called Yellow Movies), his violin performances have also achieved broad recognition. This monograph focuses on about 70 video works produced by the artist since 1977, which previously have not been systematically studied. Beginning from Conrad's earlier rather materialistic approach, in A videographic view of the artist's vita the text follows the artists shift from experimental film to a more image-driven videographic approach. The chapter Last call for video comments on Tony Conrad influential interaction with the Buffalo-based group of appropriation artists. Then Video as critique of television interrogates the interplay between (video) art and society as a reflection of the telematic culture of the 1980s. The last chapter, Video in tension with music, returns to the beginning of the artist's career and comments on Tony Conrad's identity as a musician.